2016
DOI: 10.1016/j.rmed.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine response in patients with fibrotic connective tissue disease-associated interstitial lung disease

Abstract: Background Azathioprine is a commonly prescribed therapy for connective tissue disease-associated interstitial lung disease (CTD-ILD). Combination therapy that included azathioprine was recently shown to increase the risk of death and hospitalization in patients with idiopathic pulmonary fibrosis. Whether azathioprine increases the risk of adverse outcomes in patients with fibrotic CTD-ILD, including those with CTD-associated usual interstitial pneumonia (UIP), remains unknown. Methods A retrospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 22 publications
(17 reference statements)
4
54
0
5
Order By: Relevance
“…Mycophenolate mofetil (MMF) seemed to be better tolerated as discontinuation of medication for non-pulmonary side effects was more common in patients on azathioprine (27%) than on mycophenolate (5%). The adverse incident rates were similar in the two groups and did not differ on the basis of HRCT patterns [90]. A retrospective study of 40 RA-ILD patients treated with high-dose glucocorticoids, leflunomide or methotrexate showed improvement in FVC after 4 months [91].…”
Section: Treatmentmentioning
confidence: 80%
“…Mycophenolate mofetil (MMF) seemed to be better tolerated as discontinuation of medication for non-pulmonary side effects was more common in patients on azathioprine (27%) than on mycophenolate (5%). The adverse incident rates were similar in the two groups and did not differ on the basis of HRCT patterns [90]. A retrospective study of 40 RA-ILD patients treated with high-dose glucocorticoids, leflunomide or methotrexate showed improvement in FVC after 4 months [91].…”
Section: Treatmentmentioning
confidence: 80%
“…150 While its efficacy and safety profile in CTD-ILD is comparable to newer agents such as mycophenolate, one study showed poorer tolerability due to nonrespiratory side effects. 151 Other retrospective studies support the use of azathioprine as maintenance therapy following induction therapy with cyclophosphamide. 152,153 Mycophenolate Mofetil…”
Section: Azathioprinementioning
confidence: 99%
“…Beyond SSc-ILD, more robust trial data are needed to determine the role of immunosuppressant therapy for autoimmune-associated ILDs. Although CYC, MMF, rituximab, and azathioprine are also commonly used in the treatment of RA-ILD, the evidence to support their use comes solely from retrospective or observational studies [59][60][61][62]. In a retrospective analysis of 206 patients with RA-ILD in the BRILL network, 21 had received pulsed CYC for progressive ILD; survival time was 72 months in patients treated with CYC compared with 43 months in patients with better baseline lung function who did not receive CYC [61].…”
Section: Treatment Of Autoimmune Ildsmentioning
confidence: 99%